Infrared and Terahertz Spectra of Sn-Doped Vanadium Dioxide Films - Alexander Grebenchukov; Olga Boytsova; Alexey Shakhmin; Artem Tatarenko; Olga Makarevich; Ilya Roslyakov; Grigory Kropotov; Mikhail Khodzitsky (Ceramics, 2023)
This work reports the effect of tin (Sn) doping on the infrared (IR) and terahertz (THz) properties of vanadium dioxide (VO<semantics>2</semantics>) films. The films were grown by hydrothermal synthesis with a post-annealing process and then fully characterized by X-ray diffraction (XRD), Raman spectroscopy, scanning electron microscopy (SEM), and temperature-controlled electrical resistivity as well as IR and THz spectroscopy techniques. Utilizing (NH<semantics>4</semantics>)<semantics>2</semantics>SnF<semantics>6</semantics> as a Sn precursor allows the preparation of homogeneous Sn-doped VO<semantics>2</semantics> films. Doping of VO<semantics>2</semantics> films with Sn led to an increase in the thermal hysteresis width while conserving the high modulation depth in the mid-IR regime, which would be beneficial for the applications of VO<semantics>2</semantics> films in IR memory devices. A further analysis shows that Sn doping of VO<semantics>2</semantics> films significantly affects the temperature-dependent THz optical properties, in particular leading to the suppression of the temperature-driven THz transmission modulation. These results indicate Sn-doped VO<semantics>2</semantics> films as a promising material for the development of switchable IR/THz dichroic components.